INFLUENCE OF PRODUCT QUALITY, PRODUCT DESIGN AND PROMOTION ON IPHONE PURCHASE DECISIONS ON STUDENTS IN YOGYAKARTA - Fadhilah, Muinah; Cahyani, Putri Dwi; Pratama, Alfian (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to determine the effect of product quality, product design and promotion partially and simultaneously on iPhone product purchase decisions on students in Yogyakarta. This research included correlational research. The population of this research was all Yogyakarta students who have bought iPhone products and iPhone users. The research sample was 100 respondents. Data collection techniques used a questionnaire. Data analysis technique used descriptive statistical test, classical assumption test used normality test, multicollinearity test, and heteroscedasticity test, and hypothesis test using multiple regression analysis. The results showed that there was a positive and significant effect of product quality, product design and promotion partially and simultaneously on the purchasing decisions of iPhone products for students in Yogyakarta.